Changes in Corneal Biomechanical Properties after Artiflex® and Visian® ICLV4c Implantation Using Scheimpflug-Based Noncontact Tonometer: A Comparative Analysis - Marta, Ana (2022)
INTRODUCTION : Our purpose was to compare changes in biomechanical properties after Artiflex® and Visian® ICLV4c implantation. METHODS: A prospective, nonrandomized, comparative, interventional case series study with corneal biomechanical evaluation by an ultra-high-speed Scheimpflug imaging during non-contact tonometry (Corvis ST, OCULUS®). RESULTS: The study included 38 eyes: 23 Artiflex-treated eyes and 15 implantable collamer lens (ICL)-treated eyes. The average age at surgery and the mean follow-up time were similar between groups (p=0.170 and p=0.252, respectively). Artiflex- and ICL-treated eyes showed a significantly stiffer behaviour in 12/28 and 4/28 of first and in 5/11 and 1/11 of second generation biomechanical corneal parameters compared to preoperative values, respectively. Both groupsshowed a softer behaviour in the same only 2/28 of first generation parameters. Comparing Artiflex- and ICL-treated eyes, the “PachySlope” was the only postoperative parameter that differed between groups, but the difference already exists in preoperative evaluation. All biomechanical parameters had a similar or less proportion of eyes within ectasia susceptibility interval at post-operative in both Artiflex- and ICL-treated eyes. There was a significant increase of intraocular pressure (evaluated by different methods, all with p<0.05) in Artiflex-treated eyes after surgery, compared to preoperative values. CONCLUSION: Overall it seems that there is an increase in corneal resistance after both phakic intraocular lens implantation (supported by less proportion of eyes within ectasia susceptibility interval at postoperative) or in aqueous humour resistance. The effect seems to be higher in Artiflex-treated eyes because of more postoperative biomechanical parameters changed and higher IOP (evaluated by different methods) than ICL-treated eyes, when comparing the pre and postoperative period. These findings support the safety of these surgical options for the correction of the refractive error of eyes with contraindications to laser ablation from a biomechanical viewpoint.